2017
DOI: 10.1159/000458523
|View full text |Cite
|
Sign up to set email alerts
|

Human Chorionic Gonadotropin Regression Curves after Partial or Complete Molar Pregnancy in Flanders: Are They Different from Regression Curves from the Eighties?

Abstract: Background/Aims: We updated human chorionic gonadotropin (hCG) regression curves created in the eighties after evacuation of complete and partial molar (CM and PM, respectively) pregnancies using modern hCG assays. We created similar curves for patients in need of chemotherapy (gestational trophoblastic neoplasia [GTN]). Methods: A total of 126 patients who were diagnosed with gestational trophoblastic disease from 1990 to 2014 were included. We compared curves from 2 groups, CM and PM, with historical ones. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The trend toward earlier diagnosis for both complete mole and partial mole observed in our center is consistent with the global trends as the median gestational age at evacuation was 8.75±2.30 weeks for complete mole and 9.72±3.12 weeks for partial mole. Sun et al reported The median gestational age at evacuation was 9 weeks for complete mole and 12 weeks for partial mole 38 and reported in another study 29 that the median gestational age at diagnosis continued to decrease in two non-concurrent cohorts (1988-1993 versus 1994-2013) of patients from the New England Trophoblastic Disease Center; 9 weeks versus 12 weeks. Blood transfusion was required during evacuation of 69.7% of cases of complete moles and 48.0% of partial moles.…”
Section: Discussionmentioning
confidence: 97%
“…The trend toward earlier diagnosis for both complete mole and partial mole observed in our center is consistent with the global trends as the median gestational age at evacuation was 8.75±2.30 weeks for complete mole and 9.72±3.12 weeks for partial mole. Sun et al reported The median gestational age at evacuation was 9 weeks for complete mole and 12 weeks for partial mole 38 and reported in another study 29 that the median gestational age at diagnosis continued to decrease in two non-concurrent cohorts (1988-1993 versus 1994-2013) of patients from the New England Trophoblastic Disease Center; 9 weeks versus 12 weeks. Blood transfusion was required during evacuation of 69.7% of cases of complete moles and 48.0% of partial moles.…”
Section: Discussionmentioning
confidence: 97%
“…Lybol et al [20] however reported normalization of hCG regression normograms after 3 rd and 6 th courses for single and multiple agents for patients with high risk GTN in Netherlands. Delattre et al [21] found mean time to normalization of 14-15 weeks after evacuation for complete or partial molar pregnancy in his study in Flanders. Two patients had relapse after cure and 1 died while awaiting recommencement of chemotherapy for relapse after single agent chemotherapy with methotrexate.…”
Section: Discussionmentioning
confidence: 83%
“…The reference centre advises on treatment or follow-up. hCG normalisation curves of this dataset were published previously [13].…”
Section: Belgian Register For Trophoblastic Diseasesmentioning
confidence: 99%